Sequential Capacitive Deposition of Ionic Liquids for Conformal Thin Film Coatings on Oxygen Reduction Reaction Electrocatalysts - Li, Yawei; Hart, James; Profitt, Lauren; Intikhab, Saad; Chatterjee, Swarnendu; Taheri, Mitra; Snyder, Joshua (ACS catalysis, 2019)
Ionic liquid (IL)-modified carbon-supported catalysts have demonstrated significant improvements in oxygen reduction reaction (ORR) activity. However, transition of this result from the half-cell to the proton exchange membrane fuel cell (PEMFC) has been challenging. Presented here is a processing methodology that yields the formation of a thin (<2 nm) conformal IL coating on the surface of both three-dimensional electrocatalysts and bulk single crystals through the sequential capacitive deposition (SCD) of anionic and cationic components and their subsequent condensation into a hydrophobic, protic IL. In conclusion, SCD shows promise for IL incorporation into preformed PEMFC catalyst layers.